The Influence of Digital Marketing and Lifestyle on Uniqlo Consumer Purchasing Decisions with Brand Image as a Mediating Variable (Study on Uniqlo Solo Paragon Consumers) - Nafiah, Elviana Wilda; Isa, Muzakar (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to analyze the influence of digital marketing and lifestyle on purchasing decisions with brand image as a mediating variable. This research method is quantitative. The population used is several customers who have made purchases at Uniqlo Solo Paragon with the criteria of being at least 17 years old. This research used a sample of 150 respondents. The sampling technique used was the purposive sampling method. The primary data used in this research is primary data. The data analysis techniques used in this research are descriptive and statistical analysis with SPSS version 23. The results of this research are that Digital Marketing has a positive and significant effect on Purchasing Decisions, Lifestyle has a positive and significant impact on Purchasing Decisions, Digital Marketing has a positive and significant effect on Brand Image, Lifestyle has a positive and significant impact on Brand Image, Brand Image has a positive and significant effect on Purchasing Decisions, Brand Image can mediate the relationship between Digital Marketing and Purchasing Decisions, and Brand Image can mediate the relationship between Lifestyle and Purchasing Decisions in Uniqlo Solo Paragon consumers.